2020
DOI: 10.3390/nano10020185
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Dioxide Nanoparticles Alter the Cellular Phosphoproteome in A549 Cells

Abstract: TiO2 nanoparticles (NPs) are one of the most produced NPs worldwide and are used in many consumer products. Their impact on human health, especially through inhalation, has been studied for more than two decades. TiO2 is known for its strong affinity towards phosphates, and consequently interaction with cellular phosphates may be one of the mechanisms driving its toxicity. In the present study, we used a phosphoproteomics approach to document the interaction of TiO2-NP with phosphoproteins from A549 human pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 115 publications
(175 reference statements)
0
12
1
Order By: Relevance
“…Previous in vitro and in vivo tests have confirmed the toxic effects of TiO 2 NPs on the human body like altered cell cycle, nuclear stenosis, and apoptosis [ 26 29 ]. Studies have also shown that TiO 2 NPs causes DNA damage and causes rupturing of the small intestine epithelium, which is involved in the absorption of nutrients [ 30 ]. This damage is due to various ways, mainly by inhalation, injection, and skin contact, as well as digestion and absorption [ 11 ].…”
Section: Potential Toxicity Of Tio 2 Nps and Its Amentioning
confidence: 99%
“…Previous in vitro and in vivo tests have confirmed the toxic effects of TiO 2 NPs on the human body like altered cell cycle, nuclear stenosis, and apoptosis [ 26 29 ]. Studies have also shown that TiO 2 NPs causes DNA damage and causes rupturing of the small intestine epithelium, which is involved in the absorption of nutrients [ 30 ]. This damage is due to various ways, mainly by inhalation, injection, and skin contact, as well as digestion and absorption [ 11 ].…”
Section: Potential Toxicity Of Tio 2 Nps and Its Amentioning
confidence: 99%
“…In addition, they elucidate the complexity of biological functions through statistical analyses and interpretations of bioinformatics. Recently, omics studies of NP-induced biological changes have been increasing in number [ 16 , 17 , 18 , 19 , 20 ]. Despite the high potential of targeting efficiency and the fascinating physicochemical properties of NPs, their adverse effects on cells, tissues, and organs remain a major challenge.…”
Section: Omics Approaches For the Assessment Of Nanotoxicitymentioning
confidence: 99%
“…Recently, phosphoproteomics has been applied for the assessment of nanotoxicity. For example, Biola-Clier et al reported that analysis of the phosphoproteome in TiO 2 NP-treated A549 cells showed that the TiO 2 NPs altered cellular processes such as apoptosis, cell cycle and DNA damage response, autophagy progress, RNA dynamics, and intracellular transport [ 20 ]. In particular, TiO 2 NPs affected the phosphoproteome related to their upstream regulators.…”
Section: Omics Approaches For the Assessment Of Nanotoxicitymentioning
confidence: 99%
“…NP-mediated toxicity is a rather complicated process and more factors, other than the ones we have determined, are at work. There have been numerous reports on titanium oxide [19], nanogold [20], carbon nanotubes [21], silica oxide [22], aluminum oxide [15], and cerium oxide [23] relating to cell killing. The final cell number that researchers observed was more than just the effect of cell death.…”
Section: Introductionmentioning
confidence: 99%